Oxysterol binding protein-like 3 (OSBPL3) is a novel driver gene that promotes tumor growth in part through R-Ras/Akt signaling in gastric cancer - Qingjiang Hu; Takaaki Masuda; Kensuke Koike; Kuniaki Sato; Taro Tobo; Shotaro Kuramitsu; Akihiro Kitagawa; Atsushi Fujii; Miwa Noda; Yusuke Tsuruda; Hajime Otsu; Yosuke Kuroda; et al. (Scientific Reports, 2021)
Abstract Gastric cancer (GC) is one of the most lethal malignant tumors. To improve the prognosis of GC, the identification of novel driver genes as therapeutic targets is in urgent need. Here, we aimed to identify novel driver genes and clarify their roles in gastric cancer. OSBPL3 was identified as a candidate driver gene by in silico analysis of public genomic datasets. OSBPL3 expression was analyzed by RT-qPCR and immunohistochemistry in GC cells and tissues. The biological functions and mechanisms of OSBPL3 in GC were examined in vitro and in vivo using GC cells. The association between OSBPL3 expression and clinical outcome in GC patients was also evaluated. Overexpression of OSBPL3 was detected in GC cells with OSBPL3 DNA copy number gains and promoter hypomethylation. OSBPL3-knockdown reduced GC cell growth in vitro and in vivo by inhibiting cell cycle progression. Moreover, an active Ras pull-down assay and western blotting demonstrated that OSBPL3 activates the R-Ras/Akt signaling pathway in GC cells. In a clinical analysis of two GC datasets, high OSBPL3 expression was predictive of a poor prognosis. Our findings suggest that OSBPL3 is a novel driver gene stimulating the R-Ras/Akt signaling pathway and a potential therapeutic target in GC patients.